Selective Adsorption Performance of Graphene Oxide Toward Norfloxacin and Moxifloxacin in Aqueous Solution - Amri Amri; Alfan Wijaya (Indonesian Journal of Material Research, 2025)
Norfloxacin (NFX) and moxifloxacin (MFX) are widely used fluoroquinolone antibiotics that are frequently detected as residues in aquatic environments. Their persistent presence can increase the risk of antibiotic-resistant bacteria (ARB) emerging, making the selective removal of these compounds from water systems essential. This study evaluates the adsorption selectivity of NFX and MFX using graphene oxide (GO) as a potential adsorbent. The results show that GO exhibits a higher affinity for NFX than for MFX, indicating selective interactions between the functional groups of GO and NFX molecules. These findings confirm the potential of GO as a selective adsorbent for the removal of specific antibiotics from aqueous solutions and provide a basis for developing more effective wastewater treatment strategies.